Floral structure and genetical differences of sandalwood variants in Gunung Sewu (Java, Indonesia), and its effects on breeding systems and reproductive ability - YENI W.N. RATNANINGRUM; AFFAN KURNIAWAN (Society for Indonesian Biodiversity, 2019)
Ratnaningrum YWN, Kurniawan A. 2019. Floral structure and genetical differences of sandalwood variants in Gunung Sewu (Java, Indonesia), and its effects on breeding systems and reproductive ability. Biodiversitas 20: 393-404. Our preliminary studies reported that the failure on rehabilitation program of sandalwood, an endangered endemic species in Indonesia, was caused by low viability and survival due to reproductive failure. New sandalwood landraces in Gunung Sewu Geopark, Java island consist of three variants (YBF, refers to